Advantages of using a portable cardiac monitor in outpatients with paroxysmal atrial fibrillation - M. A. Khalikova; D. A. Tsaregorodtsev; M. M. Beraya; A. V. Sedov; S. S. Vasyukov (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To study the advantages of using a portable electrocardiographic (ECG) monitor in outpatients with paroxysmal atrial fibrillation (AF).Material and methods. We examined 88 patients (26 men, 62 women, mean age, 63 [57;68] years) with paroxysmal AF with an average frequency of arrhythmia episodes of 1,0 [0.3;3.75] per month. Forty three (49%) patients were included in the remote monitoring (RM) group using the ECG Dongle monitor, and 45 (51%) patients were included in the conventional monitoring (CM) group. Patients underwent scheduled examinations 2, 6 and 12 months after the start of therapy. Unscheduled consultations were carried out in case of AF recurrence. Patients from the RM group, using portable cardiac monitor, additionally self-registered ECG 1 time per week and in case of symptoms suggestive of AF. ECG strips were sent to the clinical investigator for analysis.Results. With the help of portable cardiac monitor, 2477 ECG strips were collected and analyzed: 2159 (87,2%) — sinus rhythm, 318 (12,8%) — AF and atypical atrial flutter. Forty four episodes of AF in 3 patients were asymptomatic. In addition, 211 (8,5%) sinus rhythm ECG strips were recorded by 13 patients with symptoms suggestive of AF. In the RM group, 7 (16%) patients were hospitalized due to recurrent AF, while in the CM group, 20 (44%) patients (p=0,004). The total number of emergency hospitalizations was 8 and 29 in the RM and CM groups, respectively. The number of patients who called an ambulance was significantly lower in the RM group: in the CM group, 37 calls for an ambulance were made by 22 patients, while in the RM group — 12 patients made 15 calls (p=0,044). The proportion of calls followed by hospitalization (40 vs 70%, p=0,043) was significantly lower in the RM group.Conclusion. Remote ECG monitoring using the ECG Dongle system is a useful way to monitor patients with paroxysmal AF, which make it possible to register asymptomatic AF episodes, differentiate the causes of palpitations, and significantly reduce the frequency of emergency calls and hospitalizations.